Individual and combined application of Cu-tolerant Bacillus spp. enhance the Cu phytoextraction efficiency of perennial ryegrass. (January 2021) - Ke, Tan; Zhang, Jin; Tao, Yue; Zhang, Chao; Zhang, Yurui; Xu, Yanhong; Chen, Lanzhou
Abstract: Forage grasses have recently received a remarkable amount of attention as promising candidates for decontaminating metal-polluted soils, but this strategy is time-consuming and inefficient. The present study aimed to address the beneficial effects of screened plant growth-promoting rhizobacteria (PGPR) strains Bacillus sp. EhS5 and EhS7 on perennial ryegrass and tall fescue. Single or combined inoculation considerably increased the biomass yield and Cu content of inoculated ryegrass compared with uninoculated plants, thereby enhancing the extraction efficiency at different Cu contamination levels. Bioaugmentation did not show a positive impact on the improvement of fescue's phytoextraction efficiency. Principal component analysis (PCA) and Pearson correlation coefficient results identified root development and photosynthesis as the key variables influencing ryegrass biomass. Antioxidant activities and Cu bioavailability are the key variables influencing Cu accumulation. The inoculated ryegrass showed improved photosynthetic status as the photosystem II system efficiency parameters increased and energy dissipation in the form of heat (DIo /RC) decreased with the help of PGPR. The root length, diameter, surface area, and forks of inoculated ryegrass increased remarkably. The levels of scavengers of reactive oxygen species were enhanced in these plants. Moreover, PGPR significantly increased soil Cu bioavailability by secreting siderophores and organic acid and by increasing soil organic carbon content. Dual inoculation showed better results than individual inoculation in improving ryegrass growth and Cu translocation under high Cu contamination level according to PCA. This study systematically explored the effects and mechanisms of the Bacillus –ryegrass combined remediation and provided a novel method for cleaning Cu-contaminated sites. Graphical abstract: Image 1 Highlights: Cu-resistant Bacillus strains possessing plant growth-promoting traits, like IAA, N-fixation, and siderophores were screened. PGPR primarily modulated the root morphology and photosynthetic activity to improve ryegrass growth. PGPR enhanced antioxidant activities and Cu bioavailability to increase Cu accumulation. Bacillu s sp. EhS7 turned out to be the most effective in Cu solubilization in vitro and in vivo. The effect of co-inoculation appeared to be influenced by the Cu level and plant species.